Calcium Oxide Nanoparticles Have the Role of Alleviating Arsenic Toxicity of Barley - Nazir, Muhammad Mudassir; Li, Qi; Noman, Muhammad; Ulhassan, Zaid; Ali, Shafaqat; Ahmed, Temoor; Zeng, Fanrong; Zhang, Guoping (Frontiers in Plant Science, 2022)
Arsenic (As) contamination in agricultural soils has become a great threat to the sustainable development of agriculture and food safety. Although a lot of approaches have been proposed for dealing with soil As contamination, they are not practical in crop production due to high cost, time-taking, or operational complexity. The rapid development of nanotechnology appears to provide a novel solution to soil As contamination. This study investigated the roles of calcium oxide nanoparticles (CaO NPs) in alleviating As toxicity in two barley genotypes (LJZ and Pu-9) differing in As-tolerance. The exposure of barley seedlings to As stress showed a significant reduction in plant growth, calcium and chlorophyll content (SPAD value), fluorescence efficiency (Fv/m), and a dramatic increase in the contents of reactive oxygen species (ROS), malondialdehyde (MDA) and As, with LJZ being more affected than Pu-9. The exogenous supply of CaO NPs notably alleviated the toxic effect caused by As in the two barley genotypes. Moreover, the expression of As transporter genes, i.e., HvPHT1;1, HvPHT1;3, HvPHT1;4 and HvPHT1;6, was dramatically enhanced when barley seedlings were exposed to As stress and significantly reduced in the treatment of CaO NPs addition. It may be concluded that the roles of CaO NPs in alleviating As toxicity could be attributed to its enhancement of Ca uptake, ROS scavenging ability and reduction of As uptake and transportation from roots to shoots.